Karakteristik Penerapan Media Pembelajaran Bilingual Pada Pembelajaran Sains - Noerdjanah Noerdjanah (Jurnal Keterapian Fisik, 2017)
Abstract : Management, Learning Media, Learning Bilingual. The purposes of this study were to describe the characteristics of the application of bilingual instructional media on learning science. This research is qualitative research that is done at the fields (field research). This research used ethnography research approach characteristics. The source of data is used schools characters and overview of learning science data at SMA Batik 1 of Surakarta in drawn form, interview fieldnote, and schools document achievement. The informant in this research are the principal and teachers at SMA Batik 1 of Surakarta. The data is collected through observation, interview, and documentation. The data as analyze by using data reduction technique, data offered, and data verification/ conclusion taking. The test of data validity used credibility technique, transferability technique, dependability technique and confirmability technique. Conclusions of this research were characteristics of the implementation of bilingual instructional media on the learning of Science subject done through the preparation of learning, implementation of the learning, and evaluation of learning; Handling covers: motivate students, vocab provision to students with English, create a handbook of Science Subject with a bilingual, the use of varied teaching methods and IT-based media, and conduct the program G-SPOT On Line via radio, active students to ask the teacher of Science Subject, as well as to friends who are considered of capable, as well as doing private tutorial at foreign languages.